Litigation and Malpractice in Carpal Tunnel Surgery: An Analysis of 60 Successful Claims Over a 10-Year Period (2002–2012) - Ajwani, Sanil Harji; Hinduja, Kunal (Journal of Hand and Microsurgery, 2016)
Introduction Carpal tunnel surgery represents a significant source of litigation in hand surgery. The aim of this work was to evaluate the burden of successful litigation relating to this type of hand surgery in England. Secondary measures looked at identifying the most common causes of successful legal action.Material and Methods A retrospective review was conducted on the National Health Service Litigation Authority (NHSLA) database. All successful carpal tunnel surgery-related claims over a 10-year period from 2002 to 2012 were identified. A total of 60 claims were retrieved and analyzed.Results The total cost of successful claims to the NHS was £3.9 million. This compromised £2.4 million in damages, with £1.5 million in legal costs (22% in NHS legal costs, the remainder the claimants costs). The mean cost of settling a claim was £65,440 (range £350–£397,134). The commonest cause of the claim was nerve damage. The average damages paid in relation to this injury was £55,460. Additional surgery and poor outcome were the next commonest cause of successful proceedings, with average damages of £28,984.Conclusion Legal action in relation to carpal tunnel surgery is a considerable source of cost to hand surgeons and the NHS. The complexity of resolving these cases is reflected in the associated legal costs, which represent a significant proportion of payouts. With improved understanding of factors instigating successful legal proceedings physicians can recognize areas, where practice and training can be improved, and steps can be taken to minimize injury.
Keywords: carpal tunnel; malpractice; litigation; hand surgery